2018
DOI: 10.1016/j.jad.2018.02.074
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics and longitudinal co-occurrence of depression and different anxiety syndromes in youth: Evidence for reciprocal patterns in a 3-year prospective study

Abstract: The development of syndromes of depression, physical, and social anxiety during childhood and adolescence occurs in a predictable, systematic reciprocal pattern, rather than sequentially and unidirectionally (i.e., anxiety syndromes precede depression). Results are clinically useful for predicting risk for disorder, and demonstrate the necessity of tracking symptom levels across domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 72 publications
2
13
0
5
Order By: Relevance
“…This association has been previously described both in the general population [ 39 ], as well as in college students [ 11 ]. In fact, Long et al [ 40 ] suggest that there is a bidirectional, systematic pattern between the development of depressive and anxious syndromes in young adults. In addition, previous studies [ 41 , 42 , 43 ] have identified similarities in the neurobiology and genetic structure of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…This association has been previously described both in the general population [ 39 ], as well as in college students [ 11 ]. In fact, Long et al [ 40 ] suggest that there is a bidirectional, systematic pattern between the development of depressive and anxious syndromes in young adults. In addition, previous studies [ 41 , 42 , 43 ] have identified similarities in the neurobiology and genetic structure of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence to support both theories among adults, fewer studies have focussed on adolescents. In the extant literature, researchers have found support for the prodromal model (Cohen et al ., 2018), the bidirectional model (McLaughlin and King, 2014; Long et al ., 2018) and only homotypic pathways (e.g. depression predicts depression; Keenan et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To determine if coexistence of symptoms of anxiety and symptoms of depression would have a cumulative effect on negative attitude toward teachers and school, and poorer peer relations, we entered the two predictors into a hierarchical regression model in two steps for each of the three outcomes (Table ). To decide which predictor to be entered first, we were guided by the suggestion that anxiety‐depression coexistence commonly happen sequentially with anxiety preceding depression (Long, Young, & Hankin, ). Therefore, we first entered anxiety into the regression (Step 1) and then entered depression (Step 2).…”
Section: Resultsmentioning
confidence: 99%
“…As such, symptoms of depression statistically absorb the variance of symptoms of anxiety in predicting the outcome variables. Psychosocially, because students' school experiences encompass an affective component (Marjoribanks, 1992) and the coexistence tend to happen sequentially with anxiety preceding depression (Long et al, 2018), we speculate that the emergence of symptoms of depression signifies the further worsening of emotional wellbeing, which likely would lead to more impairment in-school experiences. Cognitively, symptoms of anxiety and depression can distort one's perception of themselves and their environment (Everaert, Duyck, & Koster, 2014;Eysenck, 1997).…”
Section: Discussionmentioning
confidence: 97%